2016
DOI: 10.1002/ange.201511351
|View full text |Cite
|
Sign up to set email alerts
|

Insights Into the Allosteric Inhibition of the SUMO E2 Enzyme Ubc9

Abstract: Conjugation of the small ubiquitin-like modifier (SUMO) to protein substrates is an important disease-associated posttranslational modification, although few inhibitors of this process are known. Herein, we report the discovery of an allosteric small-molecule binding site on Ubc9, the sole SUMO E2 enzyme.A nX -rayc rystallographic screen was used to identify two distinct small-molecule fragments that bind to Ubc9 at as ite distal to its catalytic cysteine.T hese fragments and related compounds inhibit SUMO con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
(21 reference statements)
1
6
0
Order By: Relevance
“…The E2 ligase UCB9 is responsible for the conjugation of SUMO to target molecules (35). The present study found that UBC9 was highly expressed throughout the endometrium, with no obvious changes throughout the estrous cycle.…”
Section: Protein ------------------------------------------------------------------------------------------------------------------------supporting
confidence: 46%
“…The E2 ligase UCB9 is responsible for the conjugation of SUMO to target molecules (35). The present study found that UBC9 was highly expressed throughout the endometrium, with no obvious changes throughout the estrous cycle.…”
Section: Protein ------------------------------------------------------------------------------------------------------------------------supporting
confidence: 46%
“…In addition to wild-type enzyme, two Ubc9 mutants (K59A and E42A) that disrupt a recently identified allosteric site were evaluated. 6 Compound 2 was able to inhibit SUMO conjugation to the fluorescent peptide substrate for all three enzymes without any apparent change in potency ( Suppl. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The in vitro sumoylation assay was performed in 20 µL reaction buffer (50 mM Tris [pH 9], 5 mM MgCl 2 , 1 mM DTT) containing SUMO E1 (0.1 µM), Ubc9 (0.15 µM), SUMO-1 (His-tag, 1.4 µM), and a fluorescent peptide (FL-AR) substrate 5 (1 µM) incubated with various concentrations of small molecule in DMSO or DMSO alone (4% final concentration). Experiments with mutant Ubc9, obtained as previously described, 6 were conducted according to the same procedure using K59A or E42A Ubc9 in place of the wild-type E2. The reaction was then initiated by the addition of ATP (2 mM final concentration) and incubated at room temperature for 90 min.…”
Section: Sumoylation Assaysmentioning
confidence: 99%
See 2 more Smart Citations